Rencana Reklamasi pada Lahan Bekas Tambang Galian Tras Kabupaten Probolinggo - Daffa Maulana Atthooriqh; Praditya Sigit Ardisty Sitogasa (Institut Teknologi dan Bisnis (ITB) Semarang, 2023)
Indonesia is a country rich in natural resources diversity. Utilization of natural resources can be done with mining activities. One of the natural resources that can be extracted by mining activities is Tras. Tras is a raw material for making bricks, cement, and building materials. The impact caused by mining activities is the destruction of former mining land. Management efforts that can be done are by carrying out sustainable development such as reclamation of former mining land. The purpose of this study is to plan the reclamation of Tras mining in Probolinggo Regency. Reclamation is an activity that exists throughout the stages of the mining business with the aim of organising, restoring and improving the quality of the environment and ecosystem so that it can function again according to its designation. The area to be reclaimed is 6.93 hectares. This reclamation will include landscaping, revegetation, and maintenance. Land arrangement is carried out in tandem with the process of mining and planting plants that are in accordance with the climate and soil structure such as sengon, cashew, and ketela. The former Tras excavation mining land in Probolinggo Regency will be used as productive agricultural land.